裕廊工业区发展经验极其对发展中国家的启示 = Development of Jurong Industrial Estate : lessons for the developing countries - 王文勇 Wang, Wenyong|牟果 Mu, Guo (2008)
The present study focuses on Singapore’s strategy of developing Jurong Industrial Estate in various stages, from employment creation to capital intensive to knowledge-based industries. The thesis focus on how Singapore is able to attract foreign investment despite having no natural resources.